2018 International Conference of the Biometrics Special Interest Group (BIOSIG) 2018
DOI: 10.23919/biosig.2018.8553022
|View full text |Cite
|
Sign up to set email alerts
|

Robust Clustering-based Segmentation Methods for Fingerprint Recognition

Abstract: Fingerprint recognition has been widely studied for more than 45 years and yet it remains an intriguing pattern recognition problem. This paper focuses on the foreground mask estimation which is crucial for the accuracy of a fingerprint recognition system. The method consists of a robust cluster-based fingerprint segmentation framework incorporating an additional step to deal with pixels that were rejected as foreground in a decision considered not reliable enough. These rejected pixels are then further analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The work of [21] made the model less reliant on presentation attack samples by requiring it to learn from real samples. Despite the small size of the dataset, the authors found that their model achieved better loss and accuracy, as well as lower error rates, in detecting attacks and real iris samples, despite the dataset's limited size.…”
Section: Anomaly Detectionmentioning
confidence: 99%
“…The work of [21] made the model less reliant on presentation attack samples by requiring it to learn from real samples. Despite the small size of the dataset, the authors found that their model achieved better loss and accuracy, as well as lower error rates, in detecting attacks and real iris samples, despite the dataset's limited size.…”
Section: Anomaly Detectionmentioning
confidence: 99%
“…But the segmented foreground area was slightly different from the benchmark according to the segmentation results in their paper. And in [5], an improved method for fingerprint segmentation based on the method, presented in [6], was applied. In order to make an improvement, they focused on filters and pixel clustering classification.…”
Section: Related Workmentioning
confidence: 99%
“…There still remain several limitations in the aforementioned approaches [19]. First, most existing clustering-based algorithms need to be trained in advance (e.g., [3], [7] and [15]) or require prior knowledge about the number of clusters, showed in [5], [6] and [12]. Since it's hard for online AFIS to obtain the number of clusters, those methods have difficulty in deploying their framework in practice.…”
Section: Related Workmentioning
confidence: 99%